أصــــــــــــــــــــــــل الخـــــــــــــــــــــــــطّ العـــــــــــــــــــــــــــــــربي - كحيل, عمر (University of Eloued جامعة الوادي, 2022)
يتناول المقال موضوع أصول اللغة العربية ويبحث في حيثيات ارتباطها بتاريخ الحيرة،خاصة في جانبه المادي والمتعلّق أساسًا بالشاهد الأثري الذي يؤرّخ لملك الحيرة إمرىء القيس البدء(الأول )(288-328) وأهمّية المعلومات التي جاء بها الأثر،وبيت القصيد في المقال البحث في لغة هذا الأثر وبالتحديد الخط الذي رسمت به تلك المعلومات التاريخية المهمّة،ذلك الأثر المادّي هو نقش النَّمارة . وتكمن أهمية نقش النَّمارة في كونه أقدم كتابة عربية وصلتنا،وبالتوفيق بين ما جاءت به روايات الإخباريين والمؤرخين حول الخط العربي ومن أين تعلّم العرب الخط وهذا الأثر المادي المهمّ يمكننا الوصول إلى تأكيد أن أصل الخط العربي مستمدّ من مدارس ومعلّمي الحيرة . The article deals with the subject of Arabic language origins, it also seeks for the reasons for its historical association with Al-Hirah, especially in its concrete aspect, which is the archaeological artifact that chronicles Al-Hirah’s king Imru' al-Qays (288-328).In addition to that, the importance of those pieces of information provided by that archeological evidence. and the whole point in the article is the search of the artifact language , specifically the script that was used to record those important historical pieces of information ,this artifact is The Namara inscription. The historical importance of this artifact lies in the fact that it came in the oldest Arabic script that we didn’t ever witness before. According to what stories informants and historians provided about the origin of the Arabic calligraphy, where the Arabs learned writing and what was discovered on this artifact we can deduce the confirmation that the origin of the Arabic calligraphy is taken from the schools and teachers of Al-Hirah.
مقال
Keywords: الحيرة؛المناذرة؛اللغات السامية؛الخطّ العربي؛الخطّ الحيري؛نقش النَّمارة إمرؤ القيس البدء. ; Al-hira; Almanthrah; Simitic languages; Arabic calligraphy; font of Al-hira;The Namara inscription ; Imrù al-qays.